2005
DOI: 10.1182/blood-2005-02-0807
|View full text |Cite
|
Sign up to set email alerts
|

The Shwachman-Diamond SBDS protein localizes to the nucleolus

Abstract: Shwachman-Diamond syndrome (SDS) is an autosomal recessively inherited disorder characterized by exocrine pancreatic insufficiency and bone marrow failure. The gene for this syndrome, SBDS, encodes a highly conserved novel protein. We characterized Shwachman-Bodian-Diamond syndrome (SBDS) protein expression and intracellular localization in 7 patients with SDS and healthy controls. As predicted by gene mutation, 4 patients with SDS exhibited no detectable full-length SBDS protein. Patient DF277, who was homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
119
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 44 publications
(45 reference statements)
9
119
0
3
Order By: Relevance
“…2 However, the c.258 þ 2T4C mutation, either in homozygous condition or in association with a rare mutation such as c.505C4T (p.R169C), still allows the production of some amount of normal protein. 6 This observation was recently confirmed by Nicolis et al 7 who demonstrated the presence of some amount of normal mRNA in patients carrying the c.258 þ 2T4C mutation both as compound heterozygotes (258 þ 2T4C/183_184TA4CT) and as homozygotes (258 þ 2T4C/258 þ 2T4C). In fact, when the strength of the mutated and cryptic splice sites is compared, the scores obtained support the available evidence that the mutated splice site might be partially active.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…2 However, the c.258 þ 2T4C mutation, either in homozygous condition or in association with a rare mutation such as c.505C4T (p.R169C), still allows the production of some amount of normal protein. 6 This observation was recently confirmed by Nicolis et al 7 who demonstrated the presence of some amount of normal mRNA in patients carrying the c.258 þ 2T4C mutation both as compound heterozygotes (258 þ 2T4C/183_184TA4CT) and as homozygotes (258 þ 2T4C/258 þ 2T4C). In fact, when the strength of the mutated and cryptic splice sites is compared, the scores obtained support the available evidence that the mutated splice site might be partially active.…”
Section: Discussionsupporting
confidence: 68%
“…5 A reduced but detectable quantity of the SBDS protein was shown to be present in fibroblasts of two SDS patients, this finding suggesting that the mutation found in these two cases, namely c.258 þ 2T4C, may lead to the presence of a small amount of alternatively spliced SBDS mRNA, encoding a functional protein. 6 Recently, Nicolis et al 7 demonstrated that wild-type (wt) mRNA can be found in patients carrying this mutation.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was supported by previous findings that genetic defects of ribosomal genes were implicated in congenital anemias including dyskeratosis congenita, 12 cartilage-hair hypoplasia, 13 DiamondBlackfan anemia 14 and Shwachman-Diamond syndrome. 15,16 The importance of RPS14 haplo-insufficency as a causative event in 5q-syndrome was then shown by Ebert et al using RNAi to selectively inhibit each of the 40 genes within the deleted region. 17 Suppression of RPS14 in normal CD34 + cells resulted in a 5q-syndrome like phenotype while forced expression in the hematopoietic cells of patients with 5q-syndrome rescued the phenotype.…”
mentioning
confidence: 99%
“…The SBDS gene located on chromosome 7q11 is highly conserved in archaea, plants and eukaryotes [3,16]. The protein is predicted to have 250 amino acids and gene conversion during meiosis with its neighbouring pseudogene, SBDSP (the duplicon of SBDS gene located 5·8Mb distally with nucleotide sequence homology of 97%), which results in the [17] and studies in yeast homologues suggest a role in ribosomal RNA processing [18,19]. Homozygous early truncating mutations result in complete loss in SDS function and are lethal at the embryo stage [18,20], explaining the absence of patients with such mutations.…”
Section: Discussionmentioning
confidence: 99%